LA DONACIÓN EN VIDA Y SU RESTRICCIÓN JURÍDICA EN LA LEY ORGÁNICA DE DONACIÓN Y TRASPLANTE DE ÓRGANOS, TEJIDOS Y CÉLULAS - Paladines Herrera, Diana Estefanía (2020)
The donation is the essential means for the transplantation of organs, tissues or cells. This has been proven with successes and failures in the medical field transforming and analyzing knowledge, alternative alternatives to improve or preserve the health and life of the person. The donation in life is a viable alternative that is applied in a large part of states with the net purpose of providing or facilitating organs to solve the deficit of existing anatomical components to perform transplants; These can be autotransplantation, isotransplantation or syngeneic, allogeneic and xeno- or heterotransplantation. Similarly, Ecuador applies the donation of life in a limited way and copes with the deficit of anatomical components. The realization of this work is justified mainly in the analysis of the legal restriction established in the Organic Law of Donation and Transplantation of Organs, Tissues and Cells in the year of 2011, contrary to the principle of voluntariness, the right to informed consent and multiple rights human beings enshrined in the Universal Declaration of Human Rights (1948), in the Declaration of the World Medical Association (2006), and in the Constitution of the Republic of Ecuador pertinent to living donation. The legal restriction lies in the requirement expressed in subparagraph b) of article 33 of the Organic Law of Donation and Transplantation of Organs, Tissues and Cells; which requires that the recipient must have a certain relationship of consanguinity with the donor, or establish their spouse or partner in free union and the same rule will apply for cases of filiation by adoption. Therefore, through the investigation carried out the incidence of the legal restriction of the donation in life is determined not to be governed by the universal principles of altruism, solidarity and voluntariness.